The social sonstruction of the American Street gang - Lopez-Aguado, Patrick (The Oxford handbook of gangs and society, 2024)
This chapter explores the social construction of street gangs in the United States by considering how such groups are institutionally or legally created, as well as how social meanings are ascribed to gangs as a stigmatized type of social group. Gang members build social meanings for their own groups that are often contextualized by the communities and social orders that structure their everyday lives. However, these nuanced self-definitions are often overshadowed by media depictions and legal definitions that reduce gangs to purely criminal groups. The United States’ history of using gangs as racialized folk devils have also directly shaped the heavily lopsided identification of people of color as criminal gang members. The chapter argues that, consistent with its historical use legitimizing colonial expansion and racial domination, the constructed image of the criminal gang member primarily functions as a punishable status that facilitates the conviction and mass imprisonment of poor communities of color.